Developing a Framework for Sustainable Management of Archaeological Site Parks: Cross-Case Analysis Based on Public Perception - Xi Y; Liu T; Wang Y; Ying FJ; Han Y; Luo S; Zhang P (MDPI, Basel, Switzerland, 2025)
As official terms included in the International Council on Monuments and Sites (ICOMOS) documents, archaeological site parks have gradually emphasized the establishment of sustainable management frameworks for archaeological sites open to the public and enhancing public experiences. The management frameworks should be closely related to the goals of the United Nations and other international conventions on sustainable development. However, they lack implementation strategies to promote archaeological site protection and provide responsible tourism. This research adopts a multi-case study approach to analyze the management of representative archaeological site parks in the United States, Japan, and China to develop a framework for the sustainable management of archaeological site parks. Various values, heritage tourism activities, and public perceptions of each park are examined based on cross-case analysis, which identifies principal elements and strategies for the sustainable management of archaeological parks. The principal elements reflect the archaeological parks’ intrinsic value, utility value, and other values. The strategies are closely related to the design of heritage tourism activities and are in alignment with the UN’s sustainable development goals. The theoretical and practical contributions of this research include the reflection and explanation of the sustainable management practices of archaeological site parks in different national and cultural contexts, considering public perceptions. The proposed framework and strategy integrate management guidelines, theoretical knowledge, and practical experience of public archaeological site parks. The outcomes of this research provide a reference for the study of archaeological parks and the management of heritage landscapes.